2022
DOI: 10.11591/ijere.v11i2.21987
|View full text |Cite
|
Sign up to set email alerts
|

Scientific tools for forming professional competence of patrol police officers

Abstract: <p><span lang="EN-US">In this paper, the scientific sources analysis was presented. The peculiarities of the professional competence formation of the future patrol officers were determined. Moreover, the specifics of the service activity of patrol officers were considered. The original method for the formation of professional competence of modern police officers was substantiated and tested its effectiveness. The essence of this methodology was to introduce simulated situational tasks, aimed at for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Moreover the results of scientists [3,5,27] have shown that the stability of attention, indicators of intellectual abilities and memory of servicemen and law enforcement o cers depend on the degree of development of their physical qualities (strength, static endurance of the torso muscles) and the level of general physical tness. Static endurance of the torso muscles (back and abdomen), ensuring the formation of a muscular "corset" and improving blood supply to the brain, increases the e ciency of intellectual functioning and reduces the risk of occupational diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the results of scientists [3,5,27] have shown that the stability of attention, indicators of intellectual abilities and memory of servicemen and law enforcement o cers depend on the degree of development of their physical qualities (strength, static endurance of the torso muscles) and the level of general physical tness. Static endurance of the torso muscles (back and abdomen), ensuring the formation of a muscular "corset" and improving blood supply to the brain, increases the e ciency of intellectual functioning and reduces the risk of occupational diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Today there is a signi cant expansion and complication of management tasks that require MLEAs to have a high degree of development of speci c management skills, good health, a high level of professionally important psychological and physical qualities [3,4]. The research by the scientists [5][6][7] showed that the activities of superior personnel of law enforcement agencies at all levels of management are carried out, as a rule, in di cult, and sometimes -extreme conditions. Professional management environment is accompanied by the emergence of stressful states in managers due to speci c professional relationships, unforeseen situations, instability of the socio-economic situation in the country, uncertainty about the future, shortcomings in the organization of activities of law enforcement agencies and units.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies by various scholars have focused on delineating gender-specific factors in the development of human resources for service activities within military formations and law enforcement agencies (Bondarenko, 2018;Dekanoidze & Khelashvili, 2018;Lema-Villalba et al, 2021;Medvid, 2015;Navarro-Patón et al, 2018;Stelmach et al, 2022;Torlo, 2008). It is also advisable to adapt the core theoretical tenets from these works to suit the nuances of training and to incorporate them into the educational curriculum of universities.…”
Section: Introductionmentioning
confidence: 99%
“…There is a constant need in society for the training of quali ed, highly moral and faithful to the state ideals law enforcement o cers [1][2][3][4]. Their physical training plays an important role under these circumstances [5][6][7].…”
Section: Introductionmentioning
confidence: 99%